Bioactivities and Chemical Profiling of Sesbania grandiflora (L.) Poir. Leaves Growing in Bangladesh (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The ethanolic extract of leaves of Sesbania grandiflora and their organic and aqueous soluble partitioning substances were evaluated for thrombolytic and membrane stabilizing potentials in vitro. In thrombolytic assay, among all partitionates, the ethyl acetate soluble fraction showed highest percent of clot lysis (59.57%) as compared to 69.23% and 3.07% exhibited by the standard streptokinase and water (negative control), respectively. With respect to the membrane stabilizing activity, ethyl acetate soluble fractions of S. grandiflora also profoundly inhibited the hemolysis of erythrocytes induced by osmosis (64.30 ± 0.64%) and heat (57.21 ± 0.69%), respectively. In contrast, standard acetyl salicylic acid resulted in 70.12 ± 26% inhibition of osmotically-induced hemolysis and slightly higher level of protection against heat-induced hemolysis (73.90 ± 0.29%). The ethanol extract of leaves of S. grandiflora revealed significant percentage of thrombolytic and membrane stabilizing activities.Dhaka Univ. J. Pharm. Sci. 15(2): 173-176, 2016 (December)